Looking on the bright side in social anxiety: the potential benefit of promoting positive mental imagery - Pictet, Arnaud (Frontiers in Human Neuroscience, 2014)
Current cognitive models of social phobia converge on the view that negative imagery is a key factor in the development and maintenance of the disorder. Research to date has predominantly focussed on the detrimental impact of negative imagery on cognitive bias and anxiety symptoms, while the potential benefit of promoting positive imagery has been relatively unexplored. Emerging evidence suggests however that positive imagery could have multiple benefits such as improving positive affect, self-esteem and positive interpretation bias, and enhancing social performance. The present article defends the view that combining bias induction with a repeated practice in generating positive imagery in a cognitive bias modification procedure could represent a promising area for future research and clinical innovation in social anxiety disorder.